Facial Nerve Revascularization Strategies in Facial Restoration. Issue 1 (13th January 2022) - Khajuria, Ankur; Bisase, Brian; Norris, Paul; Dhanda, Jag; Koshima, Isao; Nduka, Charles; Kannan, Ruben Y.
Abstract : Background: Facial transplants represent the current exemplar in the reconstruction of severely damaged faces, whereas conventional free flap reconstruction has its limitations in restoring both function and surface cover. Methods: In a retrospective study over 6 years (2014–2020), 5 cases (n = 5) of vascularized nerve flaps (VNFs) were performed by our team. These involved three acute and two late reconstructions. The mean age was 41 years with a maximum of 6-year follow-up. To objectify the different permutations and combinations, we categorized composite, chimeric, and hybrid VNFs into types I, IIa-c, and III, each with a unique characteristic. Postoperative function was evaluated using the validated Sunnybrook and Terzis scores for facial nerve palsy; masticatory function was assessed using dental impression studies. Results: There was a 100% flap survival rate, with no instances of flap necrosis and only one complication: hematoma at 24 hours postoperative. Sunnybrook and Terzis scores showed a statistically significant improvement postoperatively, indicating both improved repose and facial expressions (paired student t test, P < 0.05). Given that each VNF was specifically customized for a particular patient, each type of VNF in this cohort was unique, thereby illustrating each type succinctly. Conclusions: VNFs are separate entities from standard free flaps, as they require extensive preoperative planning to allow the deconstructing of composite blocks of tissue into separate vascularized entities and amalgamating them into a new conglomerate. This allows VNFs to fill a niche area in facial reconstructive surgery between face transplants and conventional free tissue transfers, with enormous potential.